Controlled growth of silicon nanocrystallites in silicon oxide matrix using 150 MeV Ag ion irradiation - Chaudhari, P. S.; Bhave, T. M.; Pasricha, R.; Singh, F.; Kanjilal, D.; Bhoraskar, S. V. (Nuclear Instruments & Methods in Physics Research Section B-Beam Interactions with Materials and Atoms, 2005)
We report the synthesis of silicon nanocrystals grown in silicon oxide matrix by swift heavy ion irradiation. Thin films of silicon oxide (SiO(x)) are irradiated with 150 MeV silver ions at fluence varying from 5 x 10(11) to 1 x 10(13) ions/cm(2). The variation in the properties of silicon nanocrystals embedded in silicon oxide with varying fluence is studied. The energy of the photoluminescence peak corresponding to the silicon nanocrystals is found to be red shifted with increasing fluence. The trends in the broadening of the X-ray diffraction peak with decreasing fluence supports the controlled growth of silicon nanocrystals in silicon oxide matrix. The crystallite size of nanoclusters of silicon is seen to increase with increasing fluence. The results are discussed in view of the structural transformation, in SiO(x) matrix, caused by swift heavy ion irradiation. (c) 2005 Elsevier B.V. All rights reserved.
Keywords: oxide matrix; silicon nanocrystallites; swift heavy ion irradiation

Mossbauer spectroscopic investigations of nanophase iron oxides synthesized by thermal plasma route - Nagar, Harshada; Kulkarni, Naveen V.; Karmakar, Soumen; Sahoo, B.; Banerjee, Indrani; Chaudhari, P. S.; Pasricha, R.; Das, A. K.; Bhoraskar, S. V.; Date, Sadgopal K.; Keune, W. (Materials Characterization, 2008)
Magnetic nanoparticles of iron oxide were synthesized by transferred arc plasma induced gas phase condensation method. Structural, morphological and magnetic studies of the as synthesized powder were carried out using X-ray diffraction, transmission electron microscopy and Mossbauer spectroscopy. These studies have revealed the simultaneous nucleation and condensation of different magnetic phases with a broad size distribution of the nanoparticles which is peaked at 30-50 nm and ranges from 10 nm to 80 nm. 57 Fe Mossbauer spectra recorded at various temperatures (5 K-300 K) in presence of external magnetic field (at 5 K) have suggested the presence of different phases of iron oxide with sizable amounts of gamma-Fe2O3 and alpha-Fe2O3 in addition to Fe3O4. The relative concentrations of these phases have been obtained by a self consistent spectral area analysis and were found to be 44:22:34 (%). (C) 2007 Elsevier Inc. All rights reserved.
Keywords: iron oxides; Mossbauer spectroscopy; phase analysis; plasma synthesis